The Effect of Deep Dialogue/Critical Thinking Model on Students’ Conceptual Understanding Ability - Bertha Jean Que; Iwan Henri Kusnadi; Ronald Maraden Parlindungan Silalahi; Arief Aulia Rahman; Andri Kurniawan (Yayasan Keluarga Guru Mandiri, 2022)
Most students in Indonesia find it difficult to understand the concepts of mathematics correctly. This is caused by the factor of teacher who doesn’t master the learning method according to the class situation and the factor of the students who are less interested in learning mathematics. The DDCT is suitable in this case, the purpose of this study is to find out the effect of the DDCT and how much it affects the students' ability to understand concepts at SMPN 7 Ambon. This research is quantitative looking for the relationship between variables, with a pre-experimental design of the type of one-shot case study. The samples taken were students of class X-1 (experimental) and X-2 (control), each of which amounted to 15 people at SMPN 7 Ambon. Data were collected on concept understanding ability tests and questionnaires used for student responses during learning using DDCT. Data were analyzed through hypothesis testing and determinant coefficients using SPSS 22.0. The results showed that the average value of the experimental class was 88.67 and the control class was 60, so there was a difference in the average value of 28.67. From the results of the analysis obtained tcount = 0.862 ttable = 0.05, it is concluded that there is an effect of DDCT on students' understanding of mathematical concepts. The findings during the research showed that DDCT: 1) can be used to train students to more easily understand a material, and 2) deep dialogue/critical thinking emphasizes attitude and mental emotional so that students learn with fun.